Coal Humanities in the Context of Counterindustrial Energy - Tomczok, Marta (Porównania, 2022)
The article presents the project of coal humanities, a multidisciplinary area of knowledge about coal, which takes into account the achievements in geology and mining, presented from the perspective of human-non-human relations, and located in energy and post-human studies. Against this background, the author first analyses the most common representations of coal in art and literature, related to industry, to show that in the mid-twentieth century, attempts were made to depart from them and create a critical reflection in Polish poetry and painting, which would be a reaction to the forced mining of coal, important for Polish economy and politics. Examples of counter-industrial representations of “green coal” are provided by the paintings of a miner from KWK “Moszczenica,” Ludwik Holesz, and the poet Bolesław Lubosz, born in Tarnowskie Góry. Both artists create visions of Carboniferous nature, try to revive coal and see something more than a raw material in it, e.g. a non-human being, a plant, and organic elements.